Export of nutrients from the Arctic Ocean. Issue 4 (3rd April 2013) - Torres‐Valdés, Sinhué; Tsubouchi, Takamasa; Bacon, Sheldon; Naveira‐Garabato, Alberto C.; Sanders, Richards; McLaughlin, Fiona A.; Petrie, Brian; Kattner, Gerhard; Azetsu‐Scott, Kumiko; Whitledge, Terry E.
Abstract: [1] This study provides the first physically based mass‐balanced transport estimates of dissolved inorganic nutrients (nitrate, phosphate, and silicate) for the Arctic Ocean. Using an inverse model‐generated velocity field in combination with a quasi‐synoptic assemblage of hydrographic and hydrochemical data, we quantify nutrient transports across the main Arctic Ocean gateways: Davis Strait, Fram Strait, the Barents Sea Opening (BSO), and Bering Strait. We found that the major exports of all three nutrients occur via Davis Strait. Transports associated with the East Greenland Current are almost balanced by transports associated with the West Spitsbergen Current. The most important imports of nitrate and phosphate to the Arctic occur via the BSO, and the most important import of silicate occurs via Bering Strait. Oceanic budgets show that statistically robust net silicate and phosphate exports exist, while the net nitrate flux is zero, within the uncertainty limits. The Arctic Ocean is a net exporter of silicate (−15.7 ± 3.2 kmol s −1 ) and phosphate (−1.0 ± 0.3 kmol s −1 ; net ± 1 standard error) to the North Atlantic. The export of excess phosphate (relative to nitrate) from the Arctic, calculated at −1.1 ± 0.3 kmol s −1, is almost twice as large as previously estimated. Net transports of silicate and phosphate from the Arctic Ocean provide 12% and 90%, respectively, of the net southward fluxes estimated at 47 ° N in the North Atlantic. Additional sources of nutrients that may offset nutrient imbalances are explored, and the relevance and the pathway of nutrient transports to the North Atlantic are discussed. Key Points: We provide physically‐based mass‐balanced Arctic nutrient transport The Arctic Ocean exports silicate and phosphate to the North Atlantic. The Arctic Ocean nitrate budget is balanced.